Anthropogenic and biogenic organic compounds in summertime fine aerosols (PM2.5) in Beijing, China. (January 2016) - Yang, Fan; Kawamura, Kimitaka; Chen, Jing; Ho, Kinfai; Lee, Shuncheng; Gao, Yuan; Cui, Long; Wang, Tieguan; Fu, Pingqing
Abstract: Ambient fine aerosol samples (PM2.5 ) were collected at an urban site (PKU) in Beijing and its upwind suburban site (Yufa) during the CAREBEIJING-2007 field campaign. Organic molecular compositions of the PM2.5 samples were studied for seven organic compound classes (sugars, lignin/resin acids, hydroxy-/polyacids, aromatic acids, biogenic SOA tracers, fatty acids and phthalates) using capillary GC/MS to better understand the characteristics and sources of organic aerosol pollution in Beijing. More than 60 individual organic species were detected in PM2.5 and were grouped into different compound classes based on their functional groups. Concentrations of total quantified organics at Yufa (469–1410 ng m −3, average 1050 ng m −3 ) were slightly higher than those at PKU (523–1390 ng m −3, 900 ng m −3 ). At both sites, phthalates were found as the most abundant compound class. Using a tracer-based method, the contributions of the biogenic secondary organic carbon (SOC) to organic carbon (OC) were 3.1% at PKU and 5.5% at Yufa, among which isoprene-SOC was the dominant contributor. In addition, most of the measured organic compounds were higher at Yufa than those at PKU, indicating a more serious pollution in its upwind region than in urban Beijing. Highlights: Anthropogenic and biogenic organic compounds have been studied in PM2.5 in Beijing. Higher levels of organic species were found in the upwind Yufa than PKU. Biogenic secondary organic carbon accounts for 3.1% of OC at PKU and 5.2% at Yufa.